Relação escola e famílias: a visão de professores e mães de alunos de classes de recuperação - Oliveira, Andréia Regina de (2004)
The aim of this study is to identify the inter-relationships established between teachers and 4th grade fundamental school pupils families that have learning difficulties and attend to parallel reinforcement classes. Took part in this study five regular 4th grade teachers, four parallel reinforcement classes teachers and six families (three of which were considered to be involved with the school and three non-involved). All children had learning difficulties and attended classes at three public schools in the town of Jaboticabal, São Paulo state, in Brazil. The instruments used for data collection were semi-structured interviews and parents evenings. The results show that the families evaluate negatively the current relationship with their children s school and point out that they would like to participate more actively, getting to know more about their children and the school as a whole. However, they see positively the school participation towards their families. The families in the study differ from the traditional mom-dad-children type of family seen as correct and normal by the teachers. The mothers in the study tend to follow the school life of their children, check their notebooks daily, ask how was the day at school and help with the homework. On the other hand, teachers judge the families as not structured and responsible for the students failures. They consider that the families oversight and are uninterested toward their children education. Teachers see their and the school s current involvement with the families as very positive, but not the other way round (they see as poor the family-school involvement). During the study it was possible to notice that the family-school communication is done mainly through notes and in the parents evenings every other month. A closer contact may happen between parents and teachers if a student eventually appears to have learning difficulties or misbehaves. It was possible to verify that the contacts are always the schools initiative and are always restrict and punctual. The families participation is restricted to the rules dictated by the school. It is the school that decides how, when and why the families should take part in the school environment. In the teachers speeches the parents-school partnership is put in evidence but there is no apparent effort from the school stimulating the parents participation in order to improve their children s performance in the same way that there is no coordinated effort to make parents act in partnership with the school.